Agricultural R&D in the developing world: too little, too late? - Pardey, Philip G.; Alston, Julian M.; Piggot, Roley R. (International Food Policy Research Institute, 2006)
The purpose of this volume is to document the changing institutions and investments in agricultural R&D in less-developed countries, in part to form a companion volume to Paying for Agricultural Productivity by providing a more complete global picture of the issues. A more important purpose is to take stock of what is happening in less-developed countries. This task is especially compelling if, as seems likely, these countries will have to become more self-reliant in developing crucial new agricultural technologies... The chapters document the history and current status of the national agricultural research systems (NARSs) in terms of policies, institutions, investments, and achievements. The case studies cover a geographically dispersed area (South Africa and China, for example) and diverse farming systems (such as Brazil vs. Korea), yet some common themes emerge... This book has been written primarily for those who make policy and allocate resources for agricultural research and extension, and the policy analysts and development specialists who advise them: specifically, strategic decision makers and their advisers in international agencies, national governments, and public or private agricultural research and extension organizations.